The generation of axially aligned seams on triangulated pipe faces. (2017) - Fogg, Harold J.; Makem, Jonathan E.; Cabello, Jean
Abstract: This paper presents a method for creating seams on pipe faces which are effective for reducing the distortion of the face flattening and thus promote the generation of high quality meshes on the faces. The method is applicable to groups of connected B-rep triangulated faces whose underlying surfaces resemble Generalised Cylinders. Isoparametric curves of Generalised Cylinder parametrisations are approximated by establishing singularity-free cross-fields starting with estimated principal curvature directions from which the seams are derived.